Efficiency Factors in the Practical Use of the Uzbek Language (Eurasian Journal of Learning and Academic Teaching, 2023)
This article, at a certain stage of the development of society, at what stage of education in each subject, what, for what purpose and in what direction, the issue of teaching has risen to the level of a national problem, and as a result, public attention to the solution of the problem, education The purpose of education is determined, the content of education is prepared, and the educational method is developed accordingly.